Entrepreneurial leadership factors: a bibliometric analysis for the 2000-2020 period - Sofia Aparisi-Torrijo; Gabriela Ribes-Giner (Management Letters/Cuadernos de Gestión, 2022)
This work aims to present an overview of the factors, attributes or behaviour of entrepreneurial leadership research with a comprehensive bibliometric analysis. 1,594 articles, dated from 2000 to December 2020, were taken from the main Web of Science database collection and analysed with a bibliometric study using performance analysis and scientific mapping methods. To evaluate the importance, quality and impact of publications, indicators like productivity, citations or h-index were used to obtain an analysis of trends and advances on the most relevant publications, authors, journals and countries. Research was complemented by scientific mapping obtained through co-citations, bibliographic couplings, co-occurrences and co-authorships. The results show that the trend of publications has considerably increased since 2015, and the highest productivity was recorded in 2020. The USA and England are two of the most influential publishing countries, although the network analysis reveals cooperation with different countries. The most productive journal is Sustainability and the most influential is the Journal of Business Venturing. This systematic mapping of the field helps to illustrate the research evolution over time, identifies areas of current interest for use in theoretical and empirical frameworks, and provides a solid roadmap for future research. The keyword analysis reveals that the term “entrepreneurial leadership” started to be used in its own right from around 2018 on average.